Comparison of polymers and ceramics in new and discarded electrical insulators: reuse and recycling possibilities - Mantovani, Vanessa Alves [UNESP]; Franco, Camila Silva; Mancini, Sandro Donnini [UNESP]; Haseagawa, Haroldo L.; Gianelli, Bruno Fernando; Batista, Vladimir Xavier; Rodrigues, Luciane Lopes (Univ Fed Rio De Janeiro, Lab Hidrogenio, 2013)
The expansion and maintenance of electricity distribution networks generates large amounts of waste, much of it in the form of discarded insulators that are not reused or recycled. This paper describes the results of tests on used and new ceramic and polymeric insulators to verify if their exposure to weathering justifies their replacement. In new and used ceramic insulators, properties such as contact angle, relative density, porosimetry, dilatometry and X-ray diffraction patterns showed no differences or the differences that were found could not be related to their use. The discarded ceramic material showed high thermal stability, an interesting characteristic for application as chamotte. It can also be reused to replace gravel used in substations. In polymeric insulators, thermogravimetry, differential scanning calorimetry and relative density test results suggest degradation of used material compared to new. This would justify their replacement and discard as waste, but they show little recycling potential.
Keywords: Electricity Network Distribution Wastes; Reuse; Recycling; Characterization Ceramics; Polymers